Median Pancreatectomy for Frantz Tumor: Management of a Splenic Artery Aneurysm by Radiological Embolization - Boubker Idrissi Kaitouni; Hamza Ouzzaouit; Talha Laalou; Hamza Sekkat; Mohamed Mahi; Ittimade Nassar; Omar El Aoufir; Youness Bakkali; Mouna Mhamdi Alaoui; Farid Sabbah; Mohammed Raiss; Abdelmalek Hrora (Case Reports in Surgery)
Iatrogenic aneurysms of the splenic artery constitute a rare yet potentially severe complication arising from diverse medical or surgical interventions. The clinical complexity and challenging management strategies associated with these aneurysms pose significant difficulties for clinicians. This circumstance is exemplified in our case report, detailing an iatrogenic aneurysm of the splenic artery that emerged secondary to a pancreatic fistula following a median pancreatectomy performed for a Frantz tumor. The intricate clinical presentation of this case underscores the considerable management challenges posed by such iatrogenic complications.